A Quantitative Study on the Role of Leadership in Facilitating Healthcare Service Delivery - Sagaren Govender; Cecile Gerwel Proches; Abdul Kader (Current Topics on Business, Economics and Finance Vol. 3, 2023)
The Department of Health in South Africa has a constitutional mandate to provide effective, efficient and quality healthcare to all citizens who reside in the country. However, the country’s healthcare system is impacted by various negative factors that hamper service delivery, particularly at regional hospitals. Consequently, the healthcare system in South Africa is in urgent need of reforms in order to provide optimal healthcare. This research examined the key service delivery challenges and the role of leadership in addressing these challenges at four public hospitals in the province of KwaZulu-Natal in South Africa. The literature review focused on current public healthcare leadership in South Africa and also attempted to draw insights from international studies. A quantitative research approach was employed in the study and stratified random sampling was used, with mid-level managers and employees constituting the sample. The results indicated that the majority of respondents agreed that leadership plays an important role in optimising organisational performance at regional hospitals. Leading with a purpose was found to be particularly important since the healthcare needs of the population are dependent upon effective and efficient healthcare service delivery. The recommendations emanating from the study could benefit healthcare leaders in that these leaders will be able to develop a better understanding of the relevance of effective leadership in public healthcare.